Developing Efficient Activation Approaches and Identifying Elements for Regional Cooperation in the Western Balkans - Vladimir Gligorov; Renate Haupfleisch; Mario Holzner; Katja Korolkova; Monika Natter; Hermine Vidovic (The Vienna Institute for International Economic Studies (wiiw), 2011)
The main objectives of this study are the assessment of activation policies in the Western Balkan countries in the light of the EU policy frameworks and the capacity and effectiveness of the Public Employment Services (PES) to implement modern labour market services. The general strategy of the research is to examine the existing activation policies against the background of labour market developments in the Western Balkan countries. In a further step the study identifies opportunities for regional cooperation among the individual countries of the region.
Keywords: C53; E24; J21; J64; J65; J68; 330; labour market; activation policies; public employment services; economic crisis; regional cooperation